Evaluation of the maturity level of BI initiatives in European higher education iInstitutions: Initial report from the BI Task Force @EUNIS - Cardoso, E.; Alcolea, J. J.; Rieger, B.; Schulze, S.; Rivera, M.; Leone, A.; Brighi, E. (19th EUNIS Congress "ICT Role for Next Generation Universities", 2013)
Business intelligence (BI) encompasses a broad category of applications and technologies for gathering, storing, analyzing, sharing and providing access to data to help enterprise users make better business decisions. Nowadays, the value of BI is perceived as more than information dissemination or tactical responses to information requests from individual managers; it is highly linked to achieving organizational goals. Therefore, well-designed and deployed BI initiatives can play an important role in organizations enabling better management, leadership and decision-making, to achieve efficiency and financial benefit.